Conversion of coffee residue waste and Eucalyptus globulus leaf extract into an alternative solid fuel. Issue 7 (3rd April 2018) - Shiferaw, Yoseph; Tedla, Abebe; Mellese, Chala; Mengistu, Atakilt; Debay, Beletie; Selamawi, Ybralem; Merene, Efoyta; Awol, Nejat
ABSTRACT: This study presents the conversion of coffee residue and Eucalyptus globulus leaf extract wastes into a solid fuel. The biochar resulting from the carbonization process was developed into a briquette charcoal form. The calorific values of the briquettes were measured by a Parr Isoperibol Bomb Calorimeter and a maximum of 6378.99 cal/g was recorded. They also demonstrated a maximum moisture content of 5.33%, fixed carbon content of 37.67%, ash content of 35%, and volatile matter of 62.50%. The briquettes showed a better quality compared to the commercially available charcoals in the study area, indicating the potential of the briquettes for use as a solid fuel. The results of this work show the prospect of reducing the volume of waste by converting it into energy.